PELAKSANAAN PROGRAM INTERVENSI PADA PENYAKIT HIPERTENSI DI PUSKESMAS PURWOYOSO KOTA SEMARANG - Addela Sekar Pramesthi Artyasari; Antono Surjoputro; Rani Tyas Budiyanti (Jurnal Kesehatan Masyarakat (Undip), 2021)
Purwoyoso Primary Health Care is a health center that has completed data collection on Healthy Indonesian Programs with Family Approaches (PIS-PK) reaching 99% in 2018. The results of the data collection showed that hypertension sufferers who seek regular treatment are still low. Purwoyoso Primary Health Care was chosen as the location for hypertension intervention and focused on RW 11 Purwoyoso Village which is the area with the lowest Healthy Family Index (IKS) due to a decrease caused by indicators of hypertension sufferers who have not reached 100%. There are three intervention programs which include the Cetar program, jemput bola, and Taman Hepi. The purpose of this study was to analyze the implementation of the PIS-PK intervention program on hypertension at Purwoyoso Health Center. This study used a qualitative method through in-depth interviews with the research subjects of the head of the Purwoyoso Health Center, hypertension program holders, program implementors, cadres, and the community. The results showed that the intervention program did not have a target indicator of success. In the Cetar and Taman hepi programs, there were insufficient resource constraints, unclear division of labor, and inadequate supervision activities. This research concludes that the variables that influence the intervention program are resources and bureaucratic structure. Purwoyoso Health Center need to develop indicators of success as benchmarks for assessment, cross-sector collaboration related to resources, training cadres, collaboration with other programs, and periodically conducting monitoring and evaluation.